Fossil Time: oil, art and the body in the cosmopolitics of the Anthropocene - Fraga (Universidade Federal do Rio de Janeiro – UFRJ, Rio de Janeiro/RJ, Brazil), Mari (Revista Brasileira de Estudos da Presença, 2022)
An artistic and theoretical investigation on fossil fuels, industrial agencies in nature and their reflections on social structures and power systems. With the goal of inspecting the operation of the arts in the cosmopolitical battles of the present especially in the new geological epoch called Anthropocene – the article analyses performance and sculpture as practices that could materialize crossings of temporalities and dimensions, reflecting on the encounter between the scales of the human and the planet. Bruno Latour’s Actor-network theory is a departing point for conceptual speculations, developed with the freedom and experimentation that moves artistic research.